Heteroresistance to Amikacin in Carbapenem-Resistant Klebsiella pneumoniae Strains - Zhang, Feiyang; Li, Qin; Bai, Jiawei; Ding, Manlin; Yan, Xiangjin; Wang, Guangxi; Zhu, Baoli; Zhou, Yingshun (Frontiers in Microbiology, 2021)
Heteroresistance can lead to treatment failure and is difficult to detect by the methods currently employed by clinical laboratories. The aim of this study was to investigate the prevalence of the amikacin-heteroresistant K. pneumoniae strains and explore potential amikacin heteroresistance mechanism through Whole-genome sequencing (WGS) and quantitative reverse-transcription PCR (qRT-PCR). In this study, thirteen isolates (8.39 %) were considered as amikacin-heteroresistant K. pneumoniae strains among a total of 155 K. pneumoniae strains. The majority of the heterogeneous phenotypes (11/13, 84.61 %) were unstable and the minimal inhibitory concentrations (MICs) fully or partially reverted back to the level of susceptibility of the parental isolate. The frequency of heteroresistant subpopulation ranged from 2.94×10-7 to 5.59×10-6. WGS and single nucleotide variants (SNVs) analysis showed that there were different nucleotide and resultant amino acid alterations among an amikacin-heteroresistant strain S38 and the resistant subpopulation S38L in several genes. Quantitative reverse-transcription PCR analysis revealed that the increased expression of aminoglycoside resistance genes detected in amikacin-heteroresistant K. pneumoniae strains might be associated with amikacin heteroresistance. The findings raise concerns for the emergence of amikacin-heteroresistant K. pneumoniae strains and the use of amikacin as therapy for the treatment of multi-drug resistant K. pneumoniae strains.